Inflammatory and deleterious role of gut microbiota-derived trimethylamine on colon cells - Jalandra, Rekha; Makharia, Govind K.; Sharma, Minakshi; Kumar, Anil (Frontiers in Immunology, 2023)
Trimethylamine (TMA) is produced by the intestinal microbiota as a by-product of choline metabolism. TMA has been implicated to various chronic health conditions. However, the effect of TMA in the colon and the underlying mechanism was not clear. In this study, TMA exhibited toxic effect in vitro as well as in vivo. TMA induced oxidative stress which causes DNA damage, compromised cell membrane integrity leading to release of LDH outside the cells which ultimately leads to cell death. Besides, TMA also exhibited pronounced increase in cell cycle arrest at G2/M phase in both HCT116 and HT29 cell line. TMA was found to be genotoxic and cytotoxic as the TMA concentration increases from 0.15 mM. A decreased ATP intracellular content was observed after 24 h, 48 h and 72 h treatment in a time and dose dependent manner. For in vivo research, TMA (100 mM, i.p. and intra-rectal) once a week for 12 weeks caused significant changes in cellular morphology of colon and rectum epithelium as assessed by H & E staining. TMA also significantly increased the infiltration of inflammatory cells in colon and rectal epithelium indicating the severity of inflammation. In addition, TMA caused extensive mucosal damage and distortion in the epithelium, decrease in length of small intestine compared to control mice. In conclusion, these results highlight the detrimental effects of TMA in colon and rectal epithelium.